Mechanochemistry-driven prelinking enables ultrahigh nitrogen-doping in carbon materials for triiodide reduction. (November 2021) - Chang, Jiangwei; Yu, Chang; Song, Xuedan; Han, Xiaotong; Ding, Yiwang; Tan, Xinyi; Li, Shaofeng; Xie, Yuanyang; Zhao, Zongbin; Qiu, Jieshan
Abstract: Nitrogen (N)-doping in graphene is now known to effectively modulate the charge density of carbon atoms, rendering the carbon materials catalytic activity. Often, the activity improves with increasing the N content. Although, as early as 2015 (Zhang et al., 2015) theoretical investigation has anticipated that it is possible to realize a high N-doping level through improving pyridinic N, by which there is still a lack of experimental verification what a doping level can be reached up to now. Herein, as a proof-of-concept study, we demonstrate, through mechanochemistry-driven prelinking to enhance the interaction between graphitic carbon nitride and graphitic lattice to preferably form pyridinic N (the maximum proportion thus obtained is 47.7%), that an ultrahigh N up to 12.4 at% is doped in the as-prepared carbon materials at a carbonization temperature up to 1000 °C. As an example, the higher N-doping can induce more carbon atoms, especially those adjacent to the pyridinic N, to be active for triiodide reduction, resulting in a wonderful power conversion efficiency of 8.86%. Graphical Abstract: We have provided a mechanochemistry-driven C-N-C prelinkage between glucose and melamine to realize high-efficiency conversion of N source to pyridinic nitrogen-dominated species, resulting in an ultrahigh doping up to 12.4 at% in the as-prepared carbon materials. As an example of application, the NCs-16 also exhibits an outstanding IRR performance with the PCE of 8.86%. ga1 Highlights: Mechanochemistry-driven prelinking enables an ultrahigh N-doping of 12.4 at% at a carbonization temperature up to 1000 o C. Pyri-N configuration is demonstrated responsible for the increasement of active site in I3 - reduction. Armchair C site near Pyri-N was evidenced as the most efficient contributor for activity.